Does the gap between health workers' expectations and the realities of implementing a performance-based financing project in Mali create frustration? - Tony Zitti; Amandine Fillol; Julia Lohmann; Abdourahmane Coulibaly; Valéry Ridde (BMC, 2021)
Abstract Background Performance-Based Financing (PBF), an innovative health financing initiative, was recently implemented in Mali. PBF aims to improve quality of care by motivating health workers. The purpose of this research was to identify and understand how health workers' expectations related to their experiences of the first cycle of payment of PBF subsidies, and how this experience affected their motivation and sentiments towards the intervention. We pose the research question, "how does the process of PBF subsidies impact the motivation of health workers in Mali?" Methods We adopted a qualitative approach using multiple case studies. We chose three district hospitals (DH 1, 2 and 3) in three health districts (district 1, 2 and 3) among the ten in the Koulikoro region. Our cases correspond to the three DHs. We followed the principle of data source triangulation; we used 53 semi-directive interviews conducted with health workers (to follow the principle of saturuation), field notes, and documents relating to the distribution grids of subsidies for each DH. We analyzed data in a mixed deductive and inductive manner. Results The results show that the PBF subsidies led to health workers feeling more motivated to perform their tasks overall. Beyond financial motivation, this was primarily due to PBF allowing them to work more efficiently. However, respondents perceived a discrepancy between the efforts made and the subsidies received. The fact that their expectations were not met led to a sense of frustration and disappointment. Similarly, the way in which the subsidies were distributed and the lack of transparency in the distribution process led to feelings of unfairness among the vast majority of respondents. The results show that frustrations can build up in the early days of the intervention. Conclusion The PBF implementation in Mali left health workers frustrated. The short overall implementation period did not allow actors to adjust their initial expectations and motivational responses, neither positive nor negative. This underlines how short-term interventions might not just lack impact, but instil negative sentiments likely to carry on into the future.